Pengaruh Promosi Jumat, Sabtu, Minggu Terhadap Keputusan Pembelian Konsumen pada Gerai Alfamart Tanjung Gusta - Manalu, Palti (LPPM Universitas Madako Tolitoli, 2025)
This study analyzes the effect of Friday, Saturday, and Sunday (JSM) promotions on consumer purchasing decisions at Alfamart Tanjung Gusta Outlets. JSM promotions are a routine marketing strategy that provides discounts on certain products. The method used in this study is a quantitative approach with data collection techniques through distributing questionnaires to consumers who shop from Friday to Sunday. The research sample consisted of 75 randomly selected respondents. The research instruments were tested for validity and reliability, and tested through classical assumptions and regression analysis using SPSS 20. The results showed that all items were declared valid and reliable, the data was normally distributed, and there were no symptoms of heteroscedasticity. However, the t-test results showed that JSM promotions did not have a significant effect on purchasing decisions partially. This finding indicates that the promotional strategy is not necessarily the main factor that drives consumers to buy. Therefore, Alfamart is advised to review its promotional communication approach to be more relevant to local consumer preferences.